2013
DOI: 10.1074/jbc.m112.428458
|View full text |Cite
|
Sign up to set email alerts
|

Sorting Nexin 1 Loss Results in D5 Dopamine Receptor Dysfunction in Human Renal Proximal Tubule Cells and Hypertension in Mice

Abstract: Background: SNX1 is a protein involved in the trafficking of internalized receptors. Results: Inhibition of SNX1 expression leads to failure of D 5 R endocytosis and signaling. Conclusion: Depletion SNX1 function results in D 5 R dysfunction and high blood pressure. Significance: Loss of SNX1 expression may be a novel mechanism for the development of hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 30 publications
(61 citation statements)
references
References 50 publications
0
61
0
Order By: Relevance
“…SNX1, SNX2, SNX4, SNX5, and SNX6 have been reported to bind to epidermal growth factor receptor, platelet-derived growth factor receptor, leptin receptor, and IR (15,32,33). We have also reported that the D 5 R signaling involves SNX1, whereas D 1 R signaling involves SNX5 (12,16). In a separate study, we found that SNX5 positively regulates the expression of the insulin degrading enzyme in hRPTCs and silencing of the SNX5 results in an increase in circulating insulin levels (our unpublished data).…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…SNX1, SNX2, SNX4, SNX5, and SNX6 have been reported to bind to epidermal growth factor receptor, platelet-derived growth factor receptor, leptin receptor, and IR (15,32,33). We have also reported that the D 5 R signaling involves SNX1, whereas D 1 R signaling involves SNX5 (12,16). In a separate study, we found that SNX5 positively regulates the expression of the insulin degrading enzyme in hRPTCs and silencing of the SNX5 results in an increase in circulating insulin levels (our unpublished data).…”
Section: Discussionmentioning
confidence: 79%
“…SNX1, SNX2, and SNX4 have been reported to regulate the cellular trafficking of receptors for epidermal growth factor, insulin, plateletderived growth factor, and leptin (15). In addition, we found that the recycling of D 5 R and D 1 R is also regulated by SNX1 and SNX5, respectively (12,16). In a separate study, we found that SNX5 also positively regulates the expression and activity of the insulin degrading enzyme; selective renal silencing of SNX5 in Wistar-Kyoto rats increases the circulating insulin levels (our unpublished data).…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…7). Agonistactivated D 1 Rs and D 5 Rs dimerize in renal epithelial cells (P. Yu and P. Jose, unpublished observations), and the impairment of one receptor results in the total absence of cAMP production in response to agonist stimulation (68,69), indicating a collaborative association between D 1 Rs and D 5 Rs. These receptors dimerize with ANG II type 2 receptors to cooperatively Fig.…”
Section: -Like Dopamine Receptor Interactions With and Regulationmentioning
confidence: 94%
“…2A). Treatment with fenoldopam redistributed some of the D 1 -like dopamine receptors to the submembrane area [we have previously reported that only around 50% of D 5 Rs internalized upon agonist activation (69)] and enhanced their colocalization with ␣ 1A -ARs. In a nonpathological section of the human kidney, all three receptors were expressed abundantly at the cytoplasm of proximal tubules, as indicated by the positive staining for the proximal tubule marker CD15, where the receptors colocalized strongly, and at the distal convoluted tubules (Fig.…”
Section: -Like Dopamine Receptors Interact With Thementioning
confidence: 98%